Profitability and Dividend Policy Analysis with Firm Size as a Moderating Variable in Determining Stock Prices of a Company - Mulyawan, Anggi; Mubarok, Faizul; Damayanti, Prisilla (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to analyze the effect of Net Profit Margin (NPM), Return on Equity (ROE), and Dividend Payout Ratio (DPR) on stock prices, with firm size as a moderating variable, in companies listed in the IDX30 index of the Indonesia Stock Exchange. The study is motivated by stock price fluctuations that do not always reflect a company’s fundamental performance. A quantitative approach was applied using secondary data from financial statements and stock prices for the 2019–2024 period. The analysis employed the Robust Least Squares (RLS) method to obtain estimates that are resistant to heteroscedasticity and extreme data. The results show that NPM has no significant effect on stock prices, while ROE and DPR have a negative and significant impact. This indicates that high ROE may signal leverage-related risk, whereas large dividend payments tend to reduce investors’ perceptions of growth potential. Firm size has a positive and significant effect on stock prices, implying that larger companies are more trusted by investors. The moderation test reveals that firm size strengthens the influence of ROE and DPR on stock prices but does not moderate the effect of NPM. These findings highlight that in large firms, equity-based profitability and dividend policy play a crucial role in determining market value.